The Arab Girl’s Pride of Her National Identity: A Reading of Suad Al-Sabah’s Poetry - Hashim, Heba Maher Attia; Alobeid, Walid (European Scientific Journal, ESJ, 2017)
The main aim of this paper is to show how the Arab girl as a spokesperson of her fellow young people in the Arab world is proud of her national identity and of her belonging to the Arab nation. This idea is clearly reflected in the poems written by the Arab poet Suad Al-Sabah who feels proud of her Arab nationalism whose heroes she glories and celebrates in her poetry; yet she blames her Arab people for going away from the true national ideals that were unifying them and providing them with power and authority. Therefore, her national voice breaks the silence of her Arab people urging them to go back to the roots of their Arab identity, the most effective remedy that can heal their present wounds. Proud of her belonging to the Arab nation, Al-Sabah looks for her national identity within the hopes and pains of her Arab homeland. Aware of her role as a spokesperson for the Arab nation as a whole, Al-Sabah as an Arab poet has decided to visit and examine the Arab past in order to praise and glorify the patriotism of her ancestors and reflect it in her poetry. This enthusiastic female speaker in her poems asserts her ability to achieve this task and speak with the national tongue of her Arab people, simply because she is an Arab from top to bottom as the female speaker in her poems proudly states.